HUBUNGAN SPIRITUAL LEADERSHIP DENGAN MANAJEMEN KEPERAWATAN : SCOOPING REVIEW - Indania, Elisabet; Suriadi, Suriadi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Spiritual leadership in nursing management is emerging as an approach that integrates spiritual values ​​with leadership practices in the health care environment. In this context, leaders not only act as decision makers, but also as mentors who motivate and inspire teams through ethical principles, empathy and a deep sense of responsibility. This research uses the Arksey and O'Malley model to carry out the analysis. Data Source: The literature analyzed consisted of Scholar, Science Direct, and Pubmed from January 2020 to June 2024. Identification and selection of literature used Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) Moher 2009. The result was 12 articles analyzed, consisting of 8 quantitative articles, 2 descriptive articles, and 2 qualitative articles. This article summarizes the findings regarding spiritual leadership in nursing management, namely that there is a relationship between spiritual leadership and performance, trust, motivation, leadership style and health services. Conclusion: There is a relationship between spiritual leadership and performance, trust, motivation, leadership style and health services.